2003
DOI: 10.1016/s0140-1971(02)00120-3
|View full text |Cite
|
Sign up to set email alerts
|

Illicit drug use, cigarette smoking and alcohol drinking behaviour among a sample of high school adolescents in the Pietersburg area of the Northern Province, South Africa

Abstract: AimThe aim of this study was to investigate the prevalence of illicit drug use, cigarette smoking and alcohol drinking behaviour among a sample of high‐school adolescents in the Pietersburg area (Central Region) of the Northern Province, South Africa.ParticipantsParticipants in this study were 435 secondary‐school adolescent students around the Pietersburg area (Central Region), in the Northern Province. Two hundred and forty‐three (56%) participants were female and 192 (44%) were male. They were aged between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
77
5
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 15 publications
19
77
5
4
Order By: Relevance
“…10,11,25 When considering substance use by gender, males in this study generally had higher prevalence rates than females. A striking finding of the Atteridgeville study is the high lifetime prevalence of alcohol use in female learners when compared with black female learners in previous South African studies.…”
Section: Discussionmentioning
confidence: 70%
“…10,11,25 When considering substance use by gender, males in this study generally had higher prevalence rates than females. A striking finding of the Atteridgeville study is the high lifetime prevalence of alcohol use in female learners when compared with black female learners in previous South African studies.…”
Section: Discussionmentioning
confidence: 70%
“…No significant sex differences were noted for other drugs (salicylates, analgesics antibiotics and stimulants) surveyed. In South Africa, a study of illicit drug use among high school adolescent 9 found that drug use, cigarette smoking and alcohol consumption are associated more with males than with females and most of the respondents do so when they are bored, tired or stressed up or at parties.…”
Section: Introductionmentioning
confidence: 99%
“…Illegal drug use among South African adolescents tends to be lower than among adolescents in the United States, with several studies reporting lifetime marijuana use rates of 6% -12% [5][6][7] A national study in the United States reported an lifetime illicit drug use rate of 19.7% among 12-17 year-olds [ 8 ]. However, since there is no national survey of drug use in South Africa, it is difficult to compare rates between the two countries.…”
Section: Introductionmentioning
confidence: 99%